Thoracolumbar compression fracture: should we brace? - Zakaria@Mohamad, Zamzuri; Goh, Kian Liang; Che Ahmad, Aminudin; Mohd Yusof, Nazri; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin (2011)
Thoracolumbar compression fracture is common following trauma. Compression fractures result from anterior or lateral flexion forces causing failure of the anterior column, sparing the middle column. Conservative treatment ranges from bracing, casting and prolonged recumbency to non-bracing with early ambulation. Previous studies have not found any significant effect comparing brace and nonbrace in term of radiological and functional outcome. We conducted a prospective randomized study to compare the outcome between bracing with Jewett brace and non-bracing with early ambulation in compression fracture of T12 to L5 with no neurological deficit. We aim to determine whether the nonbrace group will have similar outcome to the brace group in term of radiographic result, pain score and work scale at one year of follow-up.